Religious tourism in Hungary - an integrative framework - Irimiás, Anna; Michalkó, Gábor (Hungarian Geographical Bulletin, 2013)
Tourism to religious sites, shrines, temples, churches and religious festivities is significantly growing worldwide. Central and Southeastern Europe is historically a region where different ethnic and religious groups live. In the last century, during the 40 years of Communist rule over the social and political system in the Carpathian Basin, religion was banished and spiritual life could be practised mainly within the domestic environment. Since 1990, former socialist countries like Hungary (as also for example Poland, Slovakia, Romania etc.) have turned to capitalism, but without being prepared for the social, economical and psychological changes, with which that process would affect individuals and families. Faith and pilgrimages seem to have regained their roles in people's lives. This paper outlines an integrative framework on Christian religious tourism and discusses its cultural aspects. The framework emphasises the identification of geographical aspects of the phenomenon in terms of scale (local, regional, national and international) as well as in terms of the research theme (cultural, political and health-related aspects). In the first part, the history of religious tourism and its integrative framework are presented based on relevant international literature. In the second part of the paper, the focus is on the development and interpretation of the Via Maria pilgrimage route (especially at its most important station, Mátraverebély-Szentkút), the first established within the Central and Southeastern European area, and the primary results of our fi eld research are presented.